(untitled) (Comprehensive Journal of Science, 2026)
The study sought to examine the perceptions of academic and administrative staff by assessing the impact of human capital on knowledge management within the Higher Institute of Marine Sciences Technology in Sabratha. To achieve its objectives, the researcher employed a structured questionnaire as the primary data collection instrument. A descriptive-analytical methodology was adopted, supported by statistical data analysis using the SPSS software package. The study population comprised 66 members of both the academic and administrative staff. The findings indicated that human capital was rated at a high level, reflecting the Institute’s strategic emphasis on attracting qualified talent, enhancing employee competencies, and fostering collaboration and teamwork. However, certain dimensions require further development, particularly the establishment of systematic training programs and the recruitment of rare expertise. Similarly, the level of knowledge management was found to be high. Furthermore, the results demonstrated a statistically significant effect of human capital on knowledge management, underscoring the critical role of human resource capabilities in driving organizational knowledge processes.